Etnobotani Tumbuhan Pekarangan di Pemukiman Sekitar Kampus 1 UIN Jakarta, Cempaka Putih, Ciputat Timur, Tangerang Selatan - Febrianty, Alya; Amalia, Nur Dina; Ramadhyanti, Devi; Yunitasari, Nita; Nabila; Fitri, Sri Rahmadani; Kartika, Ayunda Intan; Priyanti; M., Des; Khairiah, Ardian (Prosiding Seminar Nasional Biologi, 2021)
Home garden is a part of local food systems and agricultural landscapes in the developing countries around the world. Home garden empowerment is an effort to improve and strengthen the basic economic life of the surrounding community. The purpose of this study was to determine the diversity of home garden plants, types of home gardens, plant uses, and plant habitus. Research data collection was carried out in residential area around Campus 1 of UIN Jakarta, Cempaka Putih, East Ciputat, South Tangerang within one month in April 2021 using the freelisting interview method on 30 respondents. The data was carried out by descriptive qualitative analysis. Observation results obtained as many as 504 individual plants consisting of 54 tribes, 92 genera, and 105 species originating from 30 home garden which were categorized into 3 types include front (85%), side (9%), and rear (6 %). The plants usage have been found as ornamental plants (55 species), medicinal plants (54 species), food plants (29 species), and shade plants (4 species); with type of the habitus include trees, shrubs, ferns, palms, bamboo, herbs, orchids, vines, aquatic plants, and succulents. Based on the observations, it can be concluded that the home garden in the residential areas around Campus 1 UIN Jakarta are planted with various types of plants with varying uses and habitus.